The d(9Li, p)10Li reaction as a tool to explore the 10Li structure. (July 2015) - Cavallaro, M; De Napoli, M; Cappuzzello, F; Agodi, C; Bondi, M; Carbone, D; Cunsolo, A; Davids, B; Davinson, T; Foti, A; Galinski, N; Kanungo, R; et al.
Abstract: The ground and low-lying states of the unbound nucleus 10 Li were populated by the 9 Li + 2 H → 10 Li + 1 H reaction at 11 AMeV incident energy at the ISAC II facility (TRIUMF). In the experimental setup, the outgoing 9 Li at forward angles and the recoil protons at backward angles were detected and identified. This setup allows to study the 10 Li emitted in the crucial region at forward angles in the centre of mass.